A Multi-Channel Digital Marketing Approach to Enhance Brand Awareness and Purchase Intentions in Emerging Firms - Sohaib Uz Zaman; Haiqa Tabassum; Syed Hasnain Alam (Research Journal of Psychology, 2025)
The research analyzes how emerging firms experience brand attitude and purchase intention changes from using multi-channel digital marketing approaches SEO and SMM and CM and EM. The literature gap regarding digital marketing receives comprehensive study through assessing these approaches for their combined effect on purchase choice which relies on psychological players including brand attitude and brand awareness. Digital consumers in Pakistan formed the subject of this research which used a quantitative survey approach and purposive sampling methodology to distribute 300 questionnaires among the population. A data analysis was conducted with Partial Least Squares Structural Equation Modeling (PLS-SEM) executed through SmartPLS 4.0. The model examination employed validated measure scales and assessed both direct effects as well as indirect effects that included mediated relationships and modulating factors. The study showed that content marketing and email marketing produced the greatest effect on brand attitude (β = 0.60 and β = 0.61) before brand attitude drove purchase intention at β = 0.45. The analysis demonstrated that brand awareness did not exhibit strong statistical moderation thus showing that consumer perception stands above brand visibility importance. The investigation combines Agile Marketing and COBRA frameworks in developing practical recommendations for marketers to concentrate on value-centered and emotionally driven involvement across different platforms.